Glycolysis regulates gene expression by promoting the crosstalk between H3K4 trimethylation and H3K14 acetylation in Saccharomyces cerevisiae. (20th December 2019) - Wu, Yinsheng; Zhang, Shihao; Gong, Xuanyunjing; Yu, Qi; Zhang, Yuan; Luo, Mingdan; Zhang, Xianhua; Workman, Jerry L.; Yu, Xilan; Li, Shanshan
Abstract: Cells need to coordinate gene expression with their metabolic states to maintain cell homeostasis and growth. However, how cells transduce nutrient availability to appropriate gene expression response via histone modifications remains largely unknown. Here, we report that glucose specifically induces histone H3K4 trimethylation (H3K4me3), an evolutionarily conserved histone covalent modification associated with active gene transcription, and that glycolytic enzymes and metabolites are required for this induction. Although glycolysis supplies S-adenosylmethionine for histone methyltransferase Set1 to catalyze H3K4me3, glucose induces H3K4me3 primarily by inhibiting histone demethylase Jhd2-catalyzed H3K4 demethylation. Glycolysis provides acetyl-CoA to stimulate histone acetyltransferase Gcn5 to acetylate H3K14, which then inhibits the binding of Jhd2 to chromatin to increase H3K4me3. By repressing Jhd2-mediated H3K4 demethylation, glycolytic enzymes regulate gene expression and cell survival during chronological aging. Thus, our results elucidate how cells reprogram their gene expression programs in response to glucose availability via histone modifications.